IMPLEMENTASI METODE GALLERY WALK DALAM PEMBELAJARAN MENULIS PUISI SISWA KELAS VIII SMP NUR AZIZI TANJUNG MORAWA - Luthvita Siregar, Anggun; Lubis, Malan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of the Gallery Walk method in poetry writing for eighth-grade students at Nur Azizi Junior High School, Tanjung Morawa. The research method used descriptive qualitative methods. The subjects included eighth-grade Indonesian language teachers and eighth-grade students, while the object of the study was the social situation during the implementation of the method. Data were collected through observation, interviews, and documentation techniques, which were then analyzed using the Miles and Huberman model through the stages of data reduction, data presentation, and drawing conclusions or verification. The results showed that the implementation of the Gallery Walk method was carried out systematically through the planning and implementation stages of learning. In the planning stage, teachers developed teaching modules, prepared learning materials, and arranged time allocation for activities. In the implementation stage, learning took place in line with the Gallery Walk syntax, which included dividing students into heterogeneous groups, providing worksheets and assignments, determining themes, group discussions with teacher guidance, displaying work, visiting work to observe other groups, asking questions and responding, presentations by spokespersons, joint corrections, and clarification and conclusion of learning. The results of this study are expected to serve as a reference for teachers in implementing innovative learning methods and for future researchers in studying the implementation of Indonesian language learning.